THE EFFECTIVENESS OF TEACHING MATERIALS ON ‎IMPROVING LEARNING OUTCOMES - Bahroni, Imam; Ihsan, Nur Hadi; Saifurrahman, Athifah (International Journal of Evaluation and Research in Education (IJERE), 2020)
Abstract: This study aims to determine the effectiveness of teaching books which are guidebooks for teachers in teaching on improving student learning. The study was conducted on Arabic language learning which aims to improve writing skills which is one of the four basic skills in learning Arabic. This study uses Research and Development methods (Research & Development) with methods of collecting test data, questionnaires, interviews, observation, and documentation. The method used in data analysis in this study is descriptive analysis method for qualitative data and 3 methods of data analysis for quantitative data, namely Descriptive Statistics Analysis (Analysis Statistics Descriptive), Prerequisite Test and t-Test for paired samples (Paired Samples t-Test). And the results of the analysis of product testing with the method of Descriptive Statistics Analysis, Prerequisite Test, and t-Test for paired samples indicate that this textbook is feasible and effective to be used as the main teaching material in learning Arabic on writing skills.